2009
DOI: 10.1523/jneurosci.5397-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy-Induced Smad1 Activation Promotes Axonal Growth in Adult Sensory Neurons

Abstract: Mature neurons have diminished intrinsic regenerative capacity. Axotomy of the peripheral branch of adult dorsal root ganglia (a "conditioning" lesion) triggers a transcription-dependent axon growth program. Here, we show that this growth program requires the function of the transcription factor Smad1. After peripheral axotomy, neuronal Smad1 is upregulated, and phosphorylated Smad1 accumulates in the nucleus. Both events precede the onset of axonal extension. Reducing Smad1 by RNA interference in vitro impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 29 publications
8
146
0
Order By: Relevance
“…1F) but reappears after a conditioning lesion (Fig. 1G) (15). The dynamic expression pattern of pSmad1 coincides with the changes of the intrinsic axon growth potential: embryonic and conditioned adult DRG neurons were able to extend much longer axons than adult naïve neurons in dissociated cultures ( Fig.…”
Section: Smad1 Is Developmentally Regulated In Drg Neurons and Governsmentioning
confidence: 53%
See 1 more Smart Citation
“…1F) but reappears after a conditioning lesion (Fig. 1G) (15). The dynamic expression pattern of pSmad1 coincides with the changes of the intrinsic axon growth potential: embryonic and conditioned adult DRG neurons were able to extend much longer axons than adult naïve neurons in dissociated cultures ( Fig.…”
Section: Smad1 Is Developmentally Regulated In Drg Neurons and Governsmentioning
confidence: 53%
“…Previously, through gene expression profiling, we have demonstrated that Smad1 is induced after peripheral axotomy and that intraganglionic delivery of bone morphogenetic protein 2 or 4 (BMP2 or -4) activates Smad1 and enhances the axon growth potential of adult DRG neurons in cultures. In contrast, severing the central branches of DRGs fails to activate the Smad1 pathway, which correlates with the absence of regeneration after SCI (15).…”
mentioning
confidence: 99%
“…This idea is also supported by the strong reduction of SMAD1 expression in GSK3 S/A compared with wt DRG, as neuronal SMAD1 expression levels are regulated by GSK3 activity 8 . However, as axon regeneration was promoted in GSK3 S/A mice, these data demonstrate that elevation of SMAD1 expression above basal levels in wt animals is not required for the transformation of DRG neurons into a regenerative state, without excluding the possibility that basal SMAD1 levels are essential for axon growth 37 . Interestingly, despite the overall strong reduction of SMAD1 expression in GSK3 S/A mice, expression of this transcription factor was still increased after SNC in these animals, demonstrating GSK3 phosphorylation-independent upregulation.…”
Section: Discussionmentioning
confidence: 75%
“…Unilateral sciatic nerve crush was then performed as described previously (Zhong et al, 1999). Adult DRGs were collected and cultured as described previously (Zou et al, 2009). Images were taken using a Carl Zeiss LSM710NLO confocal microscope.…”
Section: Dorsal Root Crushmentioning
confidence: 99%
“…Images were taken using a Carl Zeiss LSM710NLO confocal microscope. Axon length was quantified as described previously (Zou et al, 2009). …”
Section: Dorsal Root Crushmentioning
confidence: 99%